مدى انتشار كيسات طفيلي الجيارديا لامبليا Giardia lamblia في الحوض الأدنى من نهر الكبير الشمالي - ديوب أمل; شومان وفاء; ابراهيم سهى (Latakia University Journal -Biological Sciences Series, 2018)
Giardia lamblia is one of the most common intestinal parasites in the world and in Syria. It infects human through swimming, drinking, or eating fresh vegetables irrigated with water contaminated by waste water rich in Giardia cysts. Therefore, this research aims to investigate the prevalence of Giardia lamblia cysts in Al-kabir al-shamali river in Lattakia. Three contaminated sites were selected on the river. the first one was contaminated with waste water from some inhabited areas in Al-jinderiyah, the second site was contaminated with waste water of cow farm in the same area, and the last one was contaminated with treated waste water of Al-jinderiyah -Ein al-laban waste water treatment plant. Samples were collected from the chosen sites twice a season along September 2016 to September 2017. The microscopic examination results have revealed the presence of Giardia cysts in the three locations. The highest concentration was recorded in the first site (35 cysts L-1), followed by the second site (12 cysts L-1), and the lowest concentration was recorded in the third site (9 cysts L-1). Giardia cysts concentrations varied with seasons, the highest value was detected in Winter and the lowest one in Spring. يُعد طفيلي الجيارديا لامبليا Giardia lamblia من أكثر الطفيليات المعوية الممرضة للإنسان انتشاراً في العالم وفي سورية، وذلك لإمكانية العدوى به عن طريق تناول المياه والخضراوات أو السباحة في المياه الملوثة بالصرف الصحي الغنية بكيسات الجيارديا، لذلك هدف هذا البحث إلى التقصي عن مدى انتشار كيسات الجيارديا في نهر الكبير الشمالي بمحافظة اللاذقية. أُجريت الدراسة في ثلاثة مواقع على نهر الكبير الشمالي مختلفة بمصادر تلوثها، الموقع الأول قريب من مصب مياه صرف صحي غير معالجة (مصدر تلوث بشري مباشر), والثاني قريب من مزرعة أبقار (تلوث من مصدر حيواني), و الموقع الثالث قريب من مصب مياه الصرف الصحي المعالجة لمحطة معالجة المياه لمحور الجنديرية-عين اللبن. جُمعت العينات المائية من المواقع المدروسة, مرتين فصلياً, خلال الفترة الممتدة من أيلول 2016 ولغاية أيلول 2017. أظهرت نتائج الفحص المجهري للعينات المائية المأخوذة انتشار كيسات طفيلي الجيارديا في مياه نهر الكبير الشمالي في المواقع الثلاثة المدروسة. سُجل أعلى تركيز لها في الموقع الأول بنسبة 35 كيسة/ليتر, يليه الثاني بنسبة 12 كيسة/ليتر, فالثالث بنسبة 9 كيسة/ليتر. تباينت تراكيز كيسات الطفيلي مع تغير الفصول فبلغ أعلى تركيز لها في فصل الشتاء وأقله في الربيع وذلك في جميع المواقع المدروسة.